Social functioning in adults with visual impairment from minority ethnic communities in the United Kingdom - Heinze, Nikki; Jones, Lee (Frontiers in Public Health, 2024)
Background Visual impairment (V.I.) has been associated with a negative impact on social functioning, while social support can impact on well-being in those with V.I. Adults from minority ethnic communities (MEC) are projected to make up an increasing proportion of adults living with V.I. in the UK, but limited research has explored their social functioning. This article provides a preliminary insight into social functioning among MEC adults living with V.I. in the UK. Methods The article reports findings from a secondary analysis of V.I. Lives survey data. V.I. Lives was a UK telephone survey, which explored the life experiences of people with V.I. across a wide range of topics including social functioning. This secondary analysis explored social participation, support, isolation, and relationships among a matched control sample of 77 MEC and 77 adults aged 18 and over from White communities (WC). Participants were matched on age, gender, UK region and urban/rural setting. Subgroup analyses were also conducted for the two largest subgroups within the MEC group, Asian (n = 46) and Black participants (n = 22). Results Contact with like-minded people (U = 2174.50, p = 0.003, r = −0.24) and opportunities to take part in more social activities (U = 2253.50, p = 0.007, r = −0.22) was significantly more important to MEC than WC participants. Moreover, MEC participants were significantly less likely to feel supported by friends/family (U = 3522.50, p = 0.017, r = 0.19) and had fewer people they could ask for help (U = 3775.50, p = 0.001, r = 0.26), but there were no significant differences in the perceived impact of V.I. on their friendships/social life and marriage/relationship, their ability to take part in a range of activities, nor their marital status. Asian participants were significantly more likely than Black participants to feel cut off from the people and places around them (U = 655.50, p = 0.042, r = 0.25). Effect sizes were overall small. Although there were no further statistically significant differences between the two groups, Asian participants were also less likely to be able to take part in activities, and more likely to report a negative impact on their social life/friendships and on their marriage/relationship, as well as a smaller social network. Conclusion The findings suggest that V.I. may have had a greater impact on social functioning among Asian participants in this sample, including on experiences of social isolation and participation in social activities. Future research will need to confirm these findings and explore the possible reasons.